ANALISIS KINERJA LALU LINTAS PADA PEMBANGUNAN JEMBATAN CIPAMURUYAN - Muhamad Agung Rahman; Nunu Nugraha (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2022)
The construction of Cipamuruyan Bridge will result in increase in the traffic load. The traffic load due to the construction of the Cipamuruyan Bridge will have an impact on the performance of road network services around the construction area. Traffic performance analysis is prepared to anticipate traffic impacts that arise around the Cipamuruyan Bridge construction area. This research was carried out at the location of the planned Cipamuruyan Bridge construction on the Bogor – Sukabumi road. The data used is the volume of traffic on the Bogor - Sukabumi road which was surveyed on weekends and weekdays. The results of traffic performance analysis show that the value of the Degree of Saturation (DS) is almost the same between the current condition and the condition at the time of construction with the service level of the degree of saturation being D and E for weekends and weekdays. Meanwhile, the value of the Degree of Saturation (DS) for the current condition compared to the condition when the bridge was operational decreased by 0.481 for weekends and 0.519 for weekdays with the level of service level of saturation being B.